POTENSI MODAL PETANI DALAM MELAKUKAN PEREMAJAAN KARET DI KABUPATEN MUSI RAWAS SUMATERA SELATAN - Riantini, Maya (Jurnal AGRISEP, 2011)
The research aims to  estimate capital potencies owned by farmer for replanting their rubber plantation and optimum land size for replanting in order to get continuous income.  The research was conducted in Kelurahan Muara Beliti market, Pedang Village and Muara Beliti Village, Muara Beliti Subdistrict, Musi Rawas Regency.  These research area were chosen purposively. Using a survey approach, sisty farmers are selcted randomly using Proportionate Stratified Random Sampling and interviewed.  The data were collected from March to April 2008.  The resusearch result showed thatPotential Capital owned by farmer was Rp. 2,693,350.00 plus Rp. 5,000,00.00 as an income from selling old rubber wood so that total capital owned by farmer was Rp. 7,693,650.  From the result of analysis using Linier Programming found that the optimum replanting area of rubber was 1,883 hectare with the income of Rp. 69.351.000.  Meanwhile the human resources that were rarely found was family labor in which every unit addition of HOK will add the income of Rp. 117,000.